PENERAPAN METODE AMTSILATI SEBAGAI STRATEGI PEMBELAJARAN NAHWU DI PONDOK PESANTREN AQOBAH INTERNATIONAL SCHOOL - Wijayanto, Ryan Wahyu; Syuhadak, Syuhadak; Fitriani, Laily (Raudhah - Proud To Be Professional, 2025)
This study examines the implementation of the Amtsilati Method in Nahwu learning at Aqobah International School Islamic Boarding School. The research aims to analyze the effectiveness of this method in enhancing students' understanding of Nahwu rules. A quasi-experimental design was employed, involving two groups: an experimental group taught using the Amtsilati Method and a control group taught using conventional methods. Data were collected through pre-tests and post-tests to measure students' comprehension before and after the learning process. The experimental group underwent three structured learning sessions, focusing on step-by-step rule explanations, intensive exercises, and direct application in Arabic texts. Meanwhile, the control group followed an expository teaching model. The findings indicate that the application of the Amtsilati Method significantly improved students' Nahwu comprehension, as reflected in the higher post-test scores of the experimental group (82.00) compared to the control group (68.50). This demonstrates that the systematic and interactive approach of the Amtsilati Method effectively facilitates students' understanding of Arabic grammar.